Use of Amino-Terminal Pro–B-Type Natriuretic Peptide to Guide Outpatient Therapy of Patients With Chronic Left Ventricular Systolic Dysfunction - Januzzi, James L.; Rehman, Shafiq U.; Mohammed, Asim A.; Bhardwaj, Anju; Barajas, Linda; Barajas, Justine; Kim, Han-Na; Baggish, Aaron L.; Weiner, Rory B.; Chen-Tournoux, Annabel; Marshall, Jane E.; Moore, Stephanie A.; et al. (Journal of the American College of Cardiology, 2011)
The aim of this study was to evaluate whether chronic heart failure (HF) therapy guided by concentrations of amino-terminal pro–B-type natriuretic peptide (NT-proBNP) is superior to standard of care (SOC) management. It is unclear whether standard HF treatment plus a goal of reducing NT-proBNP concentrations improves outcomes compared with standard management alone. In a prospective single-center trial, 151 subjects with HF due to left ventricular (LV) systolic dysfunction were randomized to receive either standard HF care plus a goal to reduce NT-proBNP concentrations ≤1,000 pg/ml or SOC management. The primary endpoint was total cardiovascular events between groups compared using generalized estimating equations. Secondary endpoints included effects of NT-proBNP–guided care on patient quality of life as well as cardiac structure and function, assessed with echocardiography. Through a mean follow-up period of 10 ± 3 months, a significant reduction in the primary endpoint of total cardiovascular events was seen in the NT-proBNP arm compared with SOC (58 events vs. 100 events, p = 0.009; logistic odds for events 0.44, p = 0.02); Kaplan-Meier curves demonstrated significant differences in time to first event, favoring NT-proBNP–guided care (p = 0.03). No age interaction was found, with elderly patients benefitting similarly from NT-proBNP–guided care as younger subjects. Compared with SOC, NT-proBNP–guided patients had greater improvements in quality of life, demonstrated greater relative improvements in LV ejection fraction, and had more significant improvements in both LV end-systolic and -diastolic volume indexes. In patients with HF due to LV systolic dysfunction, NT-proBNP–guided therapy was superior to SOC, with reduced event rates, improved quality of life, and favorable effects on cardiac remodeling. (Use of NT-proBNP Testing to Guide Heart Failure Therapy in the Outpatient Setting; NCT00351390)